KARAKTERISTIK, MOTIVASI KERJA, DAN BUDAYA KERJA MEMPENGARUHI KEPUASAN KERJA (Studi Pada Rumah Sakit Umum Daerah Dr. M. Haulussy-Ambon) - Gerrit M. Pentury (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2017)
The objective of this research is to analyze the influence of the characteristics on employee job satisfaction, to analyze the influence of the work motivation on the job satisfaction of employees, to analyze the influence of the work culture on the job satisfaction of the employees.This research uses quantitative approach. This research was conducted at Dr. Regional General Hospital. M. Haulessy with a sample of permanent employees. The population in this study is permanent employees spread in all parts with the number of employees 112 people. In this study using SPSS primarily use multiple regression analysis tools in hypothesis test.The result of the research shows that the characteristic influences on the employee's pontificate, work motivation influences the employee's job satisfaction, the work culture affects the employee's job satisfaction. Keywords : Characteristics, Job Motivation, Job cultur, Job Satisfaction.